2020
DOI: 10.1063/1.5143686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface texturing on hydrodynamic lubrication at various temperatures

Abstract: The formation of hydrodynamic lubrication is analyzed based on an experimental study of the hydrodynamic lubrication characteristics between two parallel surfaces with different types of surface texturing. The study considers planar samples of C45 steel and accounts for the thermal expansion of 304 stainless steel in the experimental apparatus at oil temperatures of 323.15 K and 353.15 K. The experiments involve the use of a rotating rheometer at various angular speeds, with the effect of thermal expansion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The grooves of grating pairs at four different angles were taken and rhombohedral grid type structure was formed for each pair. The results found that all the textured samples performed better with improved load carrying capacity compared with smooth one [85].…”
Section: Newtonian Studiesmentioning
confidence: 92%
“…The grooves of grating pairs at four different angles were taken and rhombohedral grid type structure was formed for each pair. The results found that all the textured samples performed better with improved load carrying capacity compared with smooth one [85].…”
Section: Newtonian Studiesmentioning
confidence: 92%
“…In this way, the efficiency can be increased depending on the texture geometry by decreasing friction [116]. In lubricated conditions, the surface texture can increase hydrodynamic pressure, reducing friction and wear [115,117]. However, surface texturing effects are highly dependent on operating conditions, such as sliding speed or contact pressure [114].…”
Section: Surface Texturingmentioning
confidence: 99%
“…They found that the texture can display a larger oil film thickness under high-speed and heavy-duty conditions, but did not consider the lubrication performance of the texture under mixed lubrication conditions. Gao et al [12] considered the thermal expansion of lubricating oil and compared the lubrication performance of textured surfaces and untextured surfaces in specific environments through experiments. They found that the lubrication performance of textured surfaces was better than that of smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%